Antioxidant activity of bioactive peptides from peanuts protein hydrolysate - Maulidya Rachmawati; Wahyu Intan Prastiwi; Siti Narsito Wulan (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Peanut protein hydrolysate was produced from peanut protein isolate hydrolyzed using Alcalase® 2.4 L. Hydrolysis conditions were optimized using a response surface methodology. The two independent variables were the substrate/enzyme ratio and the hydrolysis time with lower and upper limits of (20:1-50:1 v/v) and (1-3 hours), respectively. Both were designed at three levels of central composite design from the response surface methodology and the degree of hydrolysis as the dependent variable. This study aimed to obtain the optimum conditions for enzymatic hydrolysis of peanut protein isolate using Alcalase to produce protein hydrolysate with the maximum degree of hydrolysis. The optimum hydrolysis conditions obtained were the substrate/enzyme ratio of 20:1 (v/v) and the  hydrolysis time of 3 hours with a predicted degree of hydrolysis of 40.54%. The actual experimental results obtained a degree of hydrolysis of 40.35% (p>0.05), which showed no difference between the predicted and experimental results. The highest antioxidant activity was obtained from the combination of these treatments, indicated by IC50 of 5.61 ppm.